Investigation of V1-xTixFeSb Semiconductor Solid Solution. II. Peculiarities of Crystal and Electronic Structure - Romaka, V.V.; Rogl, P.; Romaka, L.P.; Stadnyk, Yu.V.; Korzh, R.O.; Krayovskyy, V.Ya.; Kovbasuk, T.M.; Tsygylyk, H.V. (Physics and Chemistry of Solid State, 2015)
The peculiarities of the crystalandelectronicstructureof V1-xTixFeSb, х = 0 – 0,20, semiconductor solid solution wereinvestigated. Themechanismofgenerationofstructuraldefectsofacceptoranddonornatureisdescribed. In particular the nature of donors in n-VFeSb was established (“a priori doping”) as a result of presence of vacancies in Sb atomic site (4b). The obtained result lays in the basis of the technology for obtaining thermoelectric materials based on n-VFeSb with maximal efficiency of thermal to electrical energy conversion.